EKOLOGI MEDIA PEMBELAJARAN PAI DAN BP DI SMP ALAM BANYUWANGI - Asep Muljawan; Mohammad Ni'am Mulloh (STAI Asy-Syukriyyah, 2021)
The ecological crisis is believed to have contributed to the destruction of human survival, namely a condition in which the ecological system is disturbed or even imbalanced. Through the world of education that fosters ecological character, It is hoped that it will prove to be a viable option. to this phenomenon. The ecological character aims to increase ecological piety, considering that the ecological crises that have occurred so far are more caused by human attitudes that are not wise in interacting with their environment. Banyuwangi Alam Junior High School with the concept of nature-based learning provides a breath of fresh air for education in Indonesia in developing the character of ecological wisdom, with learning media for the ecology of PAI and BP as well as ecological interactions between students and learning media.